Mucin 16 is a functional selectin ligand on pancreatic cancer cells - Chen, Shih-Hsun (Federation of American Societies for Experimental Biology, 2012)
Selectins promote metastasis by mediating specific interactions between selectin ligands on tumor cells and selectin-expressing host cells in the microvasculature. Using affinity chromatography in conjunction with tandem mass spectrometry and bioinformatics tools, we identified mucin 16 (MUC16) as a novel selectin ligand expressed by metastatic pancreatic cancer cells. While up-regulated in many pancreatic cancers, the biological function of sialofucosylated MUC16 has yet to be fully elucidated. To address this, we employed blot rolling and cell-free flow-based adhesion assays using MUC16 immunopurified from pancreatic cancer cells and found that it efficiently binds E- and L- but not P-selectin. The selectin-binding determinants are sialofucosylated structures displayed on O- and N-linked glycans. Silencing MUC16 expression by RNAi markedly reduces pancreatic cancer cell binding to E- and L-selectin under flow. These findings provide a novel integrated perspective on the enhanced metastatic potential associated with MUC16 overexpression and the role of selectins in metastasis.—Chen, S.-H., Dallas, M. R., Balzer, E. M., Konstantopoulos, K. Mucin 16 is a functional selectin ligand on pancreatic cancer cells.